The evolution of facial length and molar proportions in cercopithecid monkeys - Monson, Tesla A.; Brasil, Marianne F. (Frontiers in Ecology and Evolution, 2025)
IntroductionPapionins are a well-studied and morphologically diverse clade of cercopithecid monkeys. Understanding how craniodental morphology varies in this clade has implications for interpreting taxonomic variation in the fossil record and for our understanding of primate evolution.MethodsWe quantified the phenotypic relationship between facial length and dental proportions in N=314 cercopithecid individuals across 10 species (six papionins, two cercopithecins, and two colobines) using dental ratios MMC (molar module component, ratio of the lengths of the third and first molars) and PMM (premolar-molar module, ratio of the lengths of the second molar and the fourth premolar) and two metrics of facial length: palatal length and prosthion – glabella.ResultsFacial length and molar dental proportions are significantly correlated interspecifically across cercopithecids (PGLS, p<0.01), where species with longer faces have relatively longer maxillary and mandibular third molars. These traits are generally not correlated intraspecifically in the cercopithecids sampled, with some exceptions.DiscussionOur data demonstrate that prognathic faces evolved convergently at least twice in papionins, with parsimony supporting that Papio/Theropithecus shared a prognathic ancestor after the divergence of Lophocebus. Additionally, this study lends support to the hypothesis that facial reduction and third molar reduction in human evolution were coordinated and may have been the result of pleiotropy alongside changes in diet.